Frequency of prescriptions of off-label drugs and drugs not approved for pediatric use in primary health care in a southern municipality of Brazil - Marcele Giacomin Gonçalves; Isabela Heineck (Sociedade de Pediatria de São Paulo, 2016)
Abstract Objective: To determine the frequency of prescriptions of off-label drugs and drugs not approved for pediatric use in primary health care in medium-sized municipality of Rio Grande do Sul, Brazil. Methods: Cross-sectional study with retrospective data collection, which analyzed prescriptions issued to 326 patients from August to December/2012 in two basic health units in the city of Viamão, state of Rio Grande do Sul. It included all prescriptions of patients whose medical records or service records were available and complete in relation to the date of presence, weight and date of birth. Off-label prescriptions were those which, in relation to the drug leaflet, showed dose different the recommended range, frequency of prescription and/or different form of administration and younger age than the indicated range. Descriptive statistics with absolute frequencies, means and standard deviations were used. Results: During the study period, a total of 731 drug prescriptions were issued and the frequency of off-label medications prescribed was 31.7%, especially antihistamines and antiasthmatics (32.3% and 31.5%, respectively). The main type of off-label prescription was dose (38.8%), followed by age range (31.5%) and frequency of administration (29.3%). Regarding the dose off-label prescription, overdose was more frequent (93.3%) than the underdose (6.7%). Prescriptions of unapproved drugs were not identified. Conclusions: The study showed that off label prescription is common in both assessed units. The observed percentage of off label prescription was higher than that reported by European studies carried out in primary care. On the other hand, the prescription of drugs not approved for children was not observed.